Increased dry season water yield in burned watersheds in Southern California - Alicia M Kinoshita; Terri S Hogue (Environmental Research Letters, 2015)
The current work evaluates the effects of the 2003 Old Fire on semi-arid systems in the San Bernardino Mountains, California. Pre- and post-fire daily streamflow are used to analyze flow regimes in two burned watersheds. The average pre-fire runoff ratios in Devil Canyon and City Creek are 0.14 and 0.26, respectively, and both increase to 0.34 post-fire. Annual flow duration curves are developed for each watershed and the low flow is characterized by a 90% exceedance probability threshold. Post-fire low flow is statistically different from the pre-fire values ( α  = 0.05). In Devil Canyon the annual volume of pre-fire low flow increases on average from 2.6E + 02 to 3.1E + 03 m ^3 (1090% increase) and in City Creek the annual low flow volume increases from 2.3E + 03 to 5.0E + 03 m ^3 (118% increase). Predicting burn system resilience to disturbance (anthropogenic and natural) has significant implications for water sustainability and ultimately may provide an opportunity to utilize extended and increased water yield.